Too Dense or Not Too Dense: Higher Planting Density Reduces Cannabinoid Uniformity but Increases Yield/Area in Drug-Type Medical Cannabis - Danziger, Nadav; Bernstein, Nirit (Frontiers in Plant Science, 2022)
A major challenge for utilizing cannabis for modern medicine is the spatial variability of cannabinoids in the plant, which entail differences in medical potency. Since secondary metabolism is affected by environmental conditions, a key trigger for the variability in secondary metabolites throughout the plant is variation in local micro-climates. We have, therefore, hypothesized that plant density, which is well-known to alter micro-climate in the canopy, affects spatial standardization, and concentrations of cannabinoids in cannabis plants. Canopy density is affected by shoot architecture and by plant spacing, and we have therefore evaluated the interplay between plant architecture and plant density on the standardization of the cannabinoid profile in the plant. Four plant architecture modulation treatments were employed on a drug-type medicinal cannabis cultivar, under a density of 1 or 2 plants/m2. The plants were cultivated in a naturally lit greenhouse with photoperiodic light supplementation. Analysis of cannabinoid concentrations at five locations throughout the plant was used to evaluate treatment effects on chemical uniformity. The results revealed an effect of plant density on cannabinoid standardization, as well as an interaction between plant density and plant architecture on the standardization of cannabinoids, thus supporting the hypothesis. Increasing planting density from 1 to 2 plants/m2 reduced inflorescence yield/plant, but increased yield quantity per area by 28–44% in most plant architecture treatments. The chemical response to plant density and architecture modulation was cannabinoid-specific. Concentrations of cannabinoids in axillary inflorescences from the bottom of the plants were up to 90% lower than in the apical inflorescence at the top of the plant, considerably reducing plant uniformity. Concentrations of all detected cannabinoids in these inflorescences were lower at the higher density plants; however, cannabinoid yield per cultivation area was not affected by neither architecture nor density treatments. Cannabigerolic acid (CBGA) was the cannabinoid least affected by spatial location in the plant. The morpho-physiological response of the plants to high density involved enhanced leaf drying at the bottom of the plants, increased plant elongation, and reduced cannabinoid concentrations, suggesting an involvement of chronic light deprivation at the bottom of the plants. Therefore, most importantly, under high density growth, architectural modulating treatments that facilitate increased light penetration to the bottom of the plant such as “Defoliation”, or that eliminated inflorescences development at the bottom of the plant such as removal of branches from the lower parts of the plant, increased chemical standardization. This study revealed the importance of plant density and architecture for chemical quality and standardization in drug-type medical cannabis.